Analisis Ketersediaan Air Pada Das Terbesar di Pulau Karimunjawa Dengan Metode Fj Mock Dimodifikasi - Elisa, Eti; Hartono, Ir.; Kusumah, Haadi (Peneliti.net, 2026)
Karimun Jawa is an archipelago located in the Java Sea and part of Jepara Regency, Central Java. With a land area of approximately 1,500 hectares and waters of approximately 110,000 hectares, Karimun Jawa is currently being developed into a marine park tourist destination that is increasingly popular with local and international tourists. This study examines water availability on small coral islands using a modified Mock method. This modification was made to suit the specific characteristics of coral islands. The research findings indicate that this method is highly efficient in predicting water availability on these very small islands, thus providing a basis for more effective water resource management planning. The analysis results show that the modified F.J. Mock method produces a water discharge of 0.0111 m³/s in January and 0.0084 m³/s in December